2015
DOI: 10.1101/gad.260349.115
|View full text |Cite
|
Sign up to set email alerts
|

Chaperoning 5S RNA assembly

Abstract: In eukaryotes, three of the four ribosomal RNAs (rRNAs)-the 5.8S, 18S, and 25S/28S rRNAs-are processed from a single pre-rRNA transcript and assembled into ribosomes. The fourth rRNA, the 5S rRNA, is transcribed by RNA polymerase III and is assembled into the 5S ribonucleoprotein particle (RNP), containing ribosomal proteins Rpl5/ uL18 and Rpl11/uL5, prior to its incorporation into preribosomes. In mammals, the 5S RNP is also a central regulator of the homeostasis of the tumor suppressor p53. The nucleolar loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 53 publications
4
74
0
2
Order By: Relevance
“…Interestingly, Rpf2, Rrs1, and Rsa4 form a network that drives formation of the final structure of H89 in rRNA domain V (Kharde et al 2015;Madru et al 2015, Wu et al 2016. Since all of these assembly factors interact with rRNA domain V in the assembling 60S subunit, our results further confirm the role of the N-terminal extension of L8 in structuring domain V (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…Interestingly, Rpf2, Rrs1, and Rsa4 form a network that drives formation of the final structure of H89 in rRNA domain V (Kharde et al 2015;Madru et al 2015, Wu et al 2016. Since all of these assembly factors interact with rRNA domain V in the assembling 60S subunit, our results further confirm the role of the N-terminal extension of L8 in structuring domain V (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…4D) and confirmed that Rrs1 interacts with the protein components of the 5S RNP and the biogenesis factor Rsa4, while Rpf2 forms extensive interactions with the 5S rRNA, uL18, and Rsa4 ( Fig. 4C,D; Kharde et al 2015;Madru et al 2015;Wu et al 2016).…”
Section: The Architecture Of the Immature Central Protuberance In Nucmentioning
confidence: 59%
“…After binding of the 5S rRNA to the ternary Syo1-uL5-uL18 complex (Kressler et al 2012a;Calviño et al 2015), the pre-assembled 5S RNP is incorporated into very early pre-ribosomal particles aided by the assembly factor complex Rpf2-Rrs1 (Zhang et al 2007). In agreement with a role in 5S RNP recruitment and stabilization of the immature CP, the Rpf2-Rrs1 complex in the Arx1 and Nog2 pre-60S particles is located at the interface between the rotated 5S RNP and the RNA helices that later form the base of the mature CP (Asano et al 2015;Kharde et al 2015;Madru et al 2015;Wu et al 2016), along with the biogenesis factor Rsa4 (Figs. 3A, 4C,D; Leidig et al 2014).…”
Section: The Architecture Of the Immature Central Protuberance In Nucmentioning
confidence: 74%
“…Formation of the 5S RNP is facilitated by the transport adaptor Syo1, which couples nuclear import of uL5 and uL18 with 5S rRNA association [90,91]. The subsequent incorporation of the 5S RNP module involves the Rpf2-Rrs1 heterodimer and has already occurred within the Nsa1-defined particle [25,86,[92][93][94] (Figure 2K). However, the exact timing and the mechanistic details of the initial 5S RNP docking to the pre-60S ribosome remain to be determined.…”
Section: Assembly Of the Lsumentioning
confidence: 99%